Immediate Effect of Jala Neti (Nasal Irrigation) on Nasal PeakInspiratory Flow on Healthy Volunteers - Rani R N; S, Prashanth; Prema Latha P; Venkateswaran S T; K, Maheshkumar (International Research Journal of Ayurveda & Yoga, 2014)
Background: Jala neti (nasal irrigation) is an ancient yogic practice believed to cleanse the nasal passages and enhance respiratory health. The objective of this study was to evaluate the immediate effect of jala neti on nasal airflow measured by peak nasal inspiratory flow (PNIF) in healthy volunteers.Methods: This was a pre-post study involving 60 healthy volunteers (16 males, 44 females) aged 18-25 years. Baseline PNIF measurements were taken before the participants performed jala neti under expert supervision. PNIF was re-measured immediately after the jala neti practice. Paired t-tests were used to compare pre and post PNIF values.Results: The mean±SD pre-neti PNIF was 84.56±12.56 L/min which increased significantly to 110.85±12.56 L/min post-neti (p=0.001). The pre and post PNIF values for males were 86.45±12.82 and 124.25±10.96 L/min respectively (p=0.02). For females, the values were 78.32±14.52 pre-neti and 98.65±12.78 L/min post-neti (p=0.04).Conclusion: Jala neti practice resulted in an immediate significant improvement in nasal inspiratory flow in healthy volunteers, suggesting it may be a beneficial practice for enhancing nasal airflow and respiratory health.